The Impact of the Ĥalāqah Method in Improving the Religious Character of Students - Nasir, Muhamad; Hartati, Zainap; Syahmidi, Syahmidi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
The aim of this research is to describe the impact of the Ĥalāqah method in improving the religious character of students at the Darul Amin Islamic boarding school in Palangka Raya. This research was carried out at the Darul Amin Palangka Raya Islamic boarding school in the form of qualitative research. Therefore, the approach taken was through a qualitative approach using the form of a case study. The source of data for this study is the teachers at Darul Amin Islamic Boarding School in Palangka Raya. Dalam penelitian ini, teknik pengumpulan data dilakukan dengan observasi, wawancara, dan dokumentasi. Adapun teknik analisis data dilakukan melalui empat tahap, yaitu pengumpulan, reduksi, penyajian, dan penarikan kesimpulan. The results of this research show that. The Ĥalāqah method at the Darul Amin Palangkaraya Islamic boarding school is used as an effort to improve the religious character of the students and to form positive interactions between the ustaz and the students, thus providing a positive impact in improving the religious character of the students.